2021
DOI: 10.1097/cm9.0000000000001369
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-23a reduces lipopolysaccharide-induced cellular apoptosis and inflammatory cytokine production through Rho-associated kinase 1/sirtuin-1/nuclear factor-kappa B crosstalk

Abstract: Background: MicroRNAs are closely associated with the progression and outcomes of multiple human diseases, including sepsis. In this study, we examined the role of miR-23a in septic injury. Methods: Lipopolysaccharide (LPS) was used to induce sepsis in a rat model and H9C2 and HK-2 cells. miR-23a expression was evaluated in rat myocardial and kidney tissues, as well as H9C2 and HK-2 cells. A miR-23a mimic was introduced into cells to identify the role of miR-23a in cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Similarly, miR-23a suppressed sepsis-induced inflammatory responses by inhibiting the SIRT1/NF-κB signaling pathway as well. 134 The inflammatory storm of cardiomyocytes in sepsis may be also caused by inhibition of phosphorylation of AMPK signaling pathway. 135 The Role of Genomics in Over-Inflammation…”
Section: Over-inflammation In Simimentioning
confidence: 99%
“…Similarly, miR-23a suppressed sepsis-induced inflammatory responses by inhibiting the SIRT1/NF-κB signaling pathway as well. 134 The inflammatory storm of cardiomyocytes in sepsis may be also caused by inhibition of phosphorylation of AMPK signaling pathway. 135 The Role of Genomics in Over-Inflammation…”
Section: Over-inflammation In Simimentioning
confidence: 99%
“…For example, during lipopolysaccharide (LPS)-induced kidney injury, the miR-23 was reduced and associated with an increase in Rho-associated kinase 1 (ROCK1). ROCK1 suppressed SIRT1, leading to the activation of NFκB [ 96 ].…”
Section: Sirt1 Expression Activity and Nad + Metab...mentioning
confidence: 99%
“…MiRNAs are potential therapeutic targets in various diseases. [ 4 ] Eight miRNAs (miRNA-1, -21, -23a, -24, -133a, -199a-3p, -214, and -378) were searched for in MEDLINE, PubMed Central, and the Human microRNA Disease Database. The reverse transcription polymerase chain reaction (RT-PCR) results showed that miRNA-1, -23a, -24, -133a, and -378 were upregulated in perfused rat hearts after MI/RI, but that luteolin pretreatment downregulated miRNA-23a and upregulated miR-378.…”
mentioning
confidence: 99%
“…MiRNAs are potential therapeutic targets in various diseases [4] . Eight miRNAs (miRNA-1, -21, -23a, -24, -133a, -199a-3p, -214, and -378) were searched for in MEDLINE, PubMed Central, and the Human microRNA Disease Database.…”
mentioning
confidence: 99%